1998
DOI: 10.1080/026990598122863
|View full text |Cite
|
Sign up to set email alerts
|

The Awareness Questionnaire: factor structure and internal consistency

Abstract: Patients with traumatic brain injuries often show impaired awareness of their impairments. This impaired awareness can decrease motivation for treatment and limit eventual functional outcome. The importance of this phenomenon has led to the development of multiple techniques and scales for measuring impaired awareness. The present paper briefly reviews the various methods of operationalizing impaired awareness and describes a new scale (the Awareness Questionnaire) designed to incorporate all these methods. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
128
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(134 citation statements)
references
References 9 publications
5
128
1
Order By: Relevance
“…Methods include comparing self-ratings to significant other or clinician ratings, such as the Patient Competency Rating Scale (PCRS) (Fleming et al, 1996;Sherer et al, 1998a), interviews (Fleming et al, 1996;Ownsworth et al, 2000), observation of actual task performance (Hart et al, 1998), comparison of patients' reports to neuropsychological performance (Allen & Ruff, 1990;Anderson & Tranel, 1989), comparison between patients' predictions of performance and actual performance (Gauggel et al, 2002;Fischer et al, 2004a) and more recently onlinemonitoring of errors (McAvinue et al, 2005;O'Keeffe et al, 2004). A number of researchers have highlighted the importance of using a number of different measures to assess the multi-faceted concept of self-awareness of deficits (Fischer et al, 2004a;Fleming et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Methods include comparing self-ratings to significant other or clinician ratings, such as the Patient Competency Rating Scale (PCRS) (Fleming et al, 1996;Sherer et al, 1998a), interviews (Fleming et al, 1996;Ownsworth et al, 2000), observation of actual task performance (Hart et al, 1998), comparison of patients' reports to neuropsychological performance (Allen & Ruff, 1990;Anderson & Tranel, 1989), comparison between patients' predictions of performance and actual performance (Gauggel et al, 2002;Fischer et al, 2004a) and more recently onlinemonitoring of errors (McAvinue et al, 2005;O'Keeffe et al, 2004). A number of researchers have highlighted the importance of using a number of different measures to assess the multi-faceted concept of self-awareness of deficits (Fischer et al, 2004a;Fleming et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Factor analysis of the AQ (Sherer et al, 1998) revealed three subscales: motor-sensory (four items), cognition (seven items), and behavioral-affective (six items).…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to these scales, Sherer et al (1998) developed the Awareness Questionnaire (AQ), consisting of 17 items that evaluate patients'current functional abilities compared with their preinjury abilities. AQ items are rated on a Likert scale ranging from 1 (much worse) to 5 (much better).…”
Section: Introductionmentioning
confidence: 99%
“…However, several authors have pointed out that lack of awareness of memory impairment is a common occurrence also in patients suffering from traumatic brain injury (TBI -Prigatano et al, 1990;Sherer et al, 1998;Bach & David, 2006;Trahan et al, 2006;Malec et al, 2007;Sherer et al, 2003;Hart et al, 2009; see also Prigatano, this issue). Tinson and Lincoln (1987) maintained that unawareness of memory problems is frequent also in stroke patients; similarly, Wilson et al (2008) pointed out that these patients often show lack of insight.…”
Section: Anosognosia For Other Deficitsmentioning
confidence: 99%
“…Tinson and Lincoln (1987) maintained that unawareness of memory problems is frequent also in stroke patients; similarly, Wilson et al (2008) pointed out that these patients often show lack of insight. Usually, assessment of anosognosia for amnesia in focal patients is based on questionnaires consisting in a series of questions about various possible deficits, including amnesia (e.g., the Patient Competency Rating Scale - Prigatano et al, 1986; the Awareness Questionnaire - Sherer et al, 1998). These represent a valuable approach to evaluate lack of awareness across different deficits, but they are clearly limited to the most evident aspects of memory deficits.…”
Section: Anosognosia For Other Deficitsmentioning
confidence: 99%